O PRAWNOKARNEJ OCHRONIE NASCITURUSA W III STATUCIE LITEWSKIM - Godek, Sławomir (Zeszyty Prawnicze, 2017)
Legal and Criminal Protection of ‘nasciturus’ in the Third Lithuanian Statute Summary The Third Lithuanian Statute of 1588 regulated the issue specified in the title only partly and quite inconsistently. On the one hand, the Third Statute introduced criminal responsibility for injuring a pregnant woman, which caused a miscarriage; nevertheless, the penalty was insignificant. On the other hand, the legislation stipulated that carrying out a capital punishment must be put off until a child’s birth, which shows the the Lithuanian legislator’s intention to respect the fetus’ right to life. The Statute also provided for the death penalty for abortion and infanticide; nevertheless - contrary to the German law applied in cities - it did notintroduce an explicit distinction between these two crimes. Another inconsistency of the Statute is a lack of punishment in case of a homicide of a bastard child.